Estudiar periodismo: un reto en medio de muchos clics - Castañeda Bustamante, Heiner (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
The article addresses the need for the profession of journalist to redefine itself within the framework of the development of Information and Communication Technologies (ICT). The author exposes the increasingly influential presence of citizen reporters, called neojournalists in the text, and the effect that this causes in the mass media, traditional carriers of the power of information, its coverage, interpretation and dissemination. According to his approaches, conceptual reflection and practical exercise are equally important elements, since the knowledge and use of multimedia and transmedia tools are essential in a universe where Internet users carry out many of the activities once intended for professional journalists, which causes the latter to wonder about the relevance of communication faculties in their training process.